Radiographic identification method of safe medial pinning zone and its clinical efficacy in pediatric supracondylar humeral fracture fixation - Liu, Hongbin; Zhu, Yong; Hu, Yi; Li, Kaihu; Long, Haitao; Lin, Zhangyuan; Zhao, Ruibo; Sun, Buhua; Zhao, Shushan; Cheng, Liang (BMC musculoskeletal disorders, 2025)
Preventing iatrogenic ulnar nerve injury remains a critical challenge during medial pinning in pediatric supracondylar humeral fractures (SCHFs). This study seeks to define a safe zone for medial pin insertion and evaluate its effectiveness in minimizing complications. Three-dimensional reconstructions of radiographs from a healthy elbow joint were generated using E3d software to delineate a safe medial pinning zone. Pediatric patients with modified Gartland type III or IV SCHFs who underwent closed reduction and percutaneous crossed pin fixation were categorized into two groups based on the medial pin entry point observed via intraoperative fluoroscopy. A retrospective analysis was performed to assess the safety and effectiveness of pin placement. Furthermore, in a case of postoperative ulnar nerve dysfunction, the standard medial pinning technique was replaced with the defined safe entry approach. On the anteroposterior (AP) view, the upper segment of the oblique line was identified as the safe zone, as the ulnar nerve lies within the groove at the lower segment. On the lateral view, a diamond-shaped area was confirmed as the safe insertion zone for medial pinning. The study included 134 SCHF cases, divided into group A (74 cases), where medial Kirschner wire (K-wire) placement was within the defined safe zones in both views, and group B (60 cases), where placement occurred outside these zones. The incidence of ulnar nerve injury in group A was significantly lower than in group B (P = 0.0324). Additionally, exploration and neurolysis were performed in cases of postoperative ulnar nerve dysfunction. A left-handed maneuver during surgery was found to aid in the precise identification of the safe entry site for medial pinning. Medial pinning performed within the delineated safe zone, with guidance from intraoperative fluoroscopy, significantly reduces the likelihood of iatrogenic ulnar nerve injury in pediatric SCHF patients. Level III retrospective comparative study.